Decellularization of ram cardiac tissue via supercritical CO2 - Cesur, Nevra Pelin; Lacin, Nelisa Turkoglu (ELSEVIER, 2022)
The decellularization method efficacy varies depending on the tissue type. There are commonly used physical, chemical and enzymatic methods. Most of the methods affect the extracellular matrix properties that will in turn alter the cell fate when the biological scaffold is recellularised. We aimed to optimize the decellularization of ram cardiac via scCO(2) extraction to preserve the moisture and the components of the ECM during the decellularization procedure. In literature decellularization studies focus on heart vessels. In this study, we aimed to decellularize and recellularize ram cardiac tissue for the first time. Besides we obtained a decellularized tissue without cells on it with a mechanical strength similar to native ECM. Decellularized ram cardiac tissue is expected to be animal-based biomaterial for candidate biomedical applications in vitro and in vivo further studies.
Keywords: Decellularization; Supercritical carbon dioxide (scCO(2)); Ram cardiac tissue; Tissue engineering and regenerative medicine; CARBON-DIOXIDE; EXTRACELLULAR-MATRIX; SCAFFOLDS; RECELLULARIZATION; EXTRACTION; Chemistry; Engineering